Overcoming minimal residual disease using intensified conditioning with medium-dose etoposide, cyclophosphamide and total body irradiation in allogeneic stem cell transplantation for Philadelphia chromosome-positive acute lymphoblastic leukemia in adults - Harada, Kaito; Morita-Fujita, Mari; Fukuda, Takahiro; Ozawa, Yukiyasu; Doki, Noriko; Toyosaki, Masako; Maruyama, Yumiko; Kanda, Yoshinobu; Ashida, Takashi; Eto, Tetsuya; Takada, Satoru; Uchida, Naoyuki; et al. (Cytotherapy (Oxford, England), 2022)
An intensified conditioning regimen incorporating medium-dose etoposide (VP16) is an option for patients with acute lymphoblastic leukemia (ALL). However, the prognostic impacts of the addition of VP16 to cyclophosphamide (CY) and total body irradiation (TBI) in patients with Philadelphia chromosome-positive (Ph+) ALL with regard to minimal residual disease (MRD) status have not been elucidated. The authors retrospectively compared the outcomes of patients with Ph+ ALL who underwent allogeneic transplantation following VP16/CY/TBI (n = 101) and CY/TBI (n = 563). At 4 years, the VP16/CY/TBI group exhibited significantly better disease-free survival (DFS) (72.6% versus 61.7%, P = 0.027) and relapse rate (11.5% versus 21.1%, P = 0.020) and similar non-relapse mortality (16.0% versus 17.2%, P = 0.70). In subgroup analyses, the beneficial effects of the addition of VP16 on DFS were more evident in patients with positive MRD status (71.2% versus 48.4% at 4 years, P = 0.022) than those with negative MRD status (72.8% versus 66.7% at 4 years, P = 0.24). Although MRD positivity was significantly associated with worse DFS in patients who received CY/TBI (48.4% versus 66.7%, P < 0.001), this was not the case in those who received VP16/CY/TBI (71.2% versus 72.8%, P = 0.86). This study demonstrated the benefits of the addition of VP16 in Ph+ ALL patients, especially those with positive MRD status. VP16/CY/TBI could be a potential strategy to overcome the survival risk of MRD positivity.